Non-linear dual stratification and modified version of heat mass flux model characteristics in magnetized Eyring Powell liquid stretched flow - M.Z. Kiyani; S. Sakhawat; S. Farooq; Mohamed H. Helal (Case Studies in Thermal Engineering)
The study investigates the magnetized dual stratified flow of a Powell-Eyring fluid within a porous medium, bounded by an inclined surface. The analysis focuses on the characteristics of heat and mass transfer, incorporating the effects of both thermal and solutal stratification. The influences of Cattaneo-Christov heat and mass flux models, thermal radiation, heat absorption/generation, and chemical reactions are examined in detail. The mathematical formulation of the problem is developed based on fundamental principles of fluid dynamics, thermodynamics, and mass transfer. Nonlinear governing differential equations are derived and subsequently transformed into a dimensionless form through suitable similarity transformations. The homotopy analysis method (HAM) is employed to obtain an analytical solution to these nonlinear equations. The HAM is also validated through the comparison with NDSolve technique. The study further explores the impact of various physical parameters, including skin friction, Schmidt number, Prandtl number, and others, on the flow, heat, and mass transfer characteristics. Graphical illustrations and theoretical discussions are provided to elucidate the behavior of these parameters and their implications on the physical phenomena under investigation. The velocity of Powell-Eyring fluid increases with higher thermal buoyancy, material, and inclination parameters, while temperature decreases with higher Prandtl number and stratification but rises with radiation and heat generation. These behaviors, alongside reduced concentration from solutal effects, have applications in industrial fluid management and thermal processes.